2013
DOI: 10.1002/jbm.a.34917
|View full text |Cite
|
Sign up to set email alerts
|

Development of an elastic cell culture substrate for a novel uniaxial tensile strain bioreactor

Abstract: Bioreactors can be used for mechanical conditioning and to investigate the mechanobiology of cells in vitro. In this study a polyurethane (PU), Chronoflex AL, was evaluated for use as a flexible cell culture substrate in a novel bioreactor capable of imparting cyclic uniaxial tensile strain to cells. PU membranes were plasma etched, across a range of operating parameters, in oxygen. Contact angle analysis and X-ray photoelectron spectroscopy showed increases in wettability and surface oxygen were related to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A similar effect is described for PU after UV irradiation in [29] and is attributed to photo-reactions. Also the XPS results showed for the PU samples irradiated by the VUV light in a N 2 or NH 3 Fig. 2 shows XPS high-resolution spectra of the C 1s level for all three cases.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…A similar effect is described for PU after UV irradiation in [29] and is attributed to photo-reactions. Also the XPS results showed for the PU samples irradiated by the VUV light in a N 2 or NH 3 Fig. 2 shows XPS high-resolution spectra of the C 1s level for all three cases.…”
Section: Methodsmentioning
confidence: 98%
“…The cell-substrate interaction under mechanical strain or compression is not only influenced by the adhesion-strength of the cell-contact to the surface, which is assumed to depend mainly on the chemistry and the micro-or nanotopography of the interface, but also directly on the rigidity of the substrate material itself [23][24][25][26]. For a systematic study of the response of cells to mechanical stimulation in vitro, cell-stretchers and adequate substrates are needed that can model the complexity of the in vivo environment and provide opportunities for examining in vitro how cells respond to different kinds of mechanical stimuli [3,18,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a stable biocompatible polyurethane (PU), Chronoflex AL 80A (AdvanSource Biomaterials, Wilmington, MA), was tested as a low modulus candidate substrate for a bioreactor capable of subjecting cells to a dynamic mechanical environment [2]. PU was selected as it is more resilient [3] and has a better cell response than similar polymers [4].…”
Section: Introductionmentioning
confidence: 99%
“…PU was selected as it is more resilient [3] and has a better cell response than similar polymers [4]. It was shown that plasma etching is a key factor to the success of cell adhesion and normal cell growth: the wettability was found to be dependent on etching power and duration, while roughness was more affected by the duration [2]. Therefore the state of oxidation of the PU membrane has been examined, in order to understand the effects of plasma etching on protein and cell adhesion.…”
Section: Introductionmentioning
confidence: 99%